Periurbanisierung: Zwischen Wohnpräferenzen und Arbeitschancen - Hilal, Mohamed; Legras, Sophie; Cavailhès, Jean (Raumforschung und Raumordnung | Spatial Research and Planning, 2018)
The debate on the nature and state of peri-urban development in Europe is dynamic. While residents and their residential preferences have long been identified as strong drivers of the process of peri-urbanisation, other influences have also been discussed, such as the supply side of the housing market or job opportunities for residents. This paper analyses the population and job growth trends in the last five decades of 230 urban areas in mainland France. The results show that the pattern of peri-urban development of all the large and medium cities of the country have strong common characteristics. In particular, the areas around cities have proven dynamic both in terms of population, as would be expected in the peri-urbanisation process described by the literature in France, but also in terms of jobs, which have been less analysed. A review of the economic literature on the determinants of firms’ location choice puts forward some of the most relevant determinants that may explain a choice of location outside central cities. This helps put in perspective the role of job opportunities in shaping peri-urbanisation in France in the recent past.